Presence of the Glossosomatidae in Madagascar, with description of two species (Trichoptera) - Gibon, François-Marie (Zootaxa, 2017)
Two new species of Agapetus Curtis, 1834 are described from Madagascar: Agapetus (Synagapetus) alarum n. sp. from the Andringitra National Park and Agapetus (Synagapetus) ranohelae n. sp. from the Andohahela National Park. They are the first species of Agapetus reported from the Island and belong to the southern African Agapetus (Synagapetus) agilis Species Group.